The Next Generation Social Welfare Information System (SIKS – NG) Website Acceptance Model in Garut Regency using UTAUT 3 - Fauziyyah, Nadhira; Alamanda, Dini Turipanam; Ramdhani, Abdullah; Kusmiati, Eti (PINISI Discretion Review, 2024)
Increasing user acceptance of a website is an important aspect in ensuring the success and sustainability of website usage. In Garut Regency, the implementation of the Next Generation Social Welfare Information System (SIKS – NG) plays a crucial role in providing population information services to the public. Therefore, this research aims to analyse the acceptance model of the SIKS – NG website in Garut Regency using the Unified Theory of Acceptance and Use of Technology 3 (UTAUT 3). This study employed a survey method by collecting data from 40 users representing sub-districts in Garut Kota District t, Garut Regency. The data were then analysed using Partial Least Squares – Structural Equation Mode (PLS – SEM). The result showed that performance expectations, business expectations, habits, facilitating conditions and personal computer innovation which are the dimensions of UTAUT 3 have a significant effect on behavioural intention and there is an influence of behavioural intention on SIKS – NG website adoption behaviour in Garut Regency. This research has practical implications the development and management of the SIKS – NG website, especially in Garut Regency. In addition, this research can also be a basis for further research in the context of the acceptance use of information technology in other areas.